2019
DOI: 10.12659/aot.914690
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Relapse Following Liver Transplantation for Alcoholic Liver Disease

Abstract: Background Alcohol use disorders affect 10% of the European population. Alcohol-related liver disease (ALD) is the most common indication for liver transplantation in Slovakia. The aim of this study was to determine the proportion of patients with ALD who received a liver transplant who had alcohol relapsed, and the risk factors for alcohol relapse, as well as to compare clinical outcomes according to relapse. Material/Methods A retrospective study of consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
(51 reference statements)
2
12
1
Order By: Relevance
“…Prior studies have identified various parameters that are heterogeneously correlated with alcohol abuse after liver transplantation, such as tobacco smoking [2,26], social status/support [2,26], time since transplantation [2], age [5], and psychiatric comorbidity [26]. In our study, there was no significant difference for most of these factors between the uEtG negative and the uEtG positive group.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Prior studies have identified various parameters that are heterogeneously correlated with alcohol abuse after liver transplantation, such as tobacco smoking [2,26], social status/support [2,26], time since transplantation [2], age [5], and psychiatric comorbidity [26]. In our study, there was no significant difference for most of these factors between the uEtG negative and the uEtG positive group.…”
Section: Discussioncontrasting
confidence: 48%
“…The impact of alcohol abuse after liver transplantation is best documented in patients transplanted for alcoholic liver disease (ALD). In these patients, alcohol relapse can lead to diminished graft survival as well as contribute to reduced patient survival, especially when higher amounts of alcohol (>30 g/day) are consumed [1][2][3][4][5]. Furthermore, alcohol abuse is associated with reduced patient compliance and the occurrence of nonhepatic cancers, which further endanger graft and patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…For example, hepatitis C viremia, pre-direct acting antiviral therapy, was common post-transplant, and greater than 20% of patients with alcohol related liver disease will relapse after transplant. [ 34 ] PSC, which was higher in these populations, is also prone to recurrence. [ 35 ] Overall, this data suggests that graft survival is similar among ethnicities despite differences in rates of rejection episodes and disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers have a 79% higher risk of dying compared to nonsmokers[ 115 ]. A history of smoking is not only a well-known risk factor leading to the major causes of death in the long-term post-LT, such as development of cardiovascular complications and de novo neoplasms, as showed by a recent meta-analysis[ 118 ], but it has also been associated with alcohol relapse in ALD-transplanted patients[ 119 ], recurrent viral-hepatitis[ 120 ], an augmented risk of IBD flare in PSC-transplanted patients[ 121 ], and with an increase in biliary complications[ 122 ]. On the other hand, an increased time from smoking cessation to transplantation seems to be a protective factor against developing biliary complications[ 123 ].…”
Section: Smokingmentioning
confidence: 99%